Enhanced conversion of Glycerol to Glycerol carbonate on modified Bio-Char from reed plant: Enhanced conversion of Glycerol to Glycerol carbonate on modified Bio-Char from reed plant - Mohamed, Shafaa Dhyaa; J. Ahmed, Muthana (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
The surplus glycerol produced from biodiesel production process as a by-product with high quantity can be considered as a good source to prepare glycerol carbonate (GC) whereas with each 1000 kg from biodiesel obtains 100 kg from glycerol. Glycerol converted to glycerol carbonate over bio-char as a catalyst prepared by slow pyrolysis process under various temperatures from 400 ᴼC to 800 ᴼC. The char prepared at 700 ᴼC considered as a best one between the others which was manufactured to activate the transesterification reaction. GC have large scale of uses such as liquid membrane in gas separation, surfactants ,detergents , blowing agent , in plastics industry, in Pharmaceutical industry and electrolytes in lithium batteries. Yield percent of GC is 9.3% without catalyze the reaction with char whereas in case of bio-char used the GC yield increases to 67.80%. When the catalyst modified with 3 molar concentration of sodium hydroxide, the yield of glycerol carbonate obtained 98.3% and complete conversion. All the reaction in this study performed under conditions 60ᴼC, 90 min, 3:1 DMC:G and 3%wt. catalyst loading.